Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

Near‐zero growth kinetics of P seudomonas putida deduced from proteomic analysis - Nicolai S. Panikov; Manolis Mandalakis; Shujia Dai; Lawrence R. Mulcahy; William Fowle; Wendy S. Garrett; Barry L. Karger (Environmental Microbiology, 2015)
Summary Intensive microbial growth typically observed in laboratory rarely occurs in nature. Because of severe nutrient deficiency, natural populations exhibit near‐zero growth ( NZG ). There is a long‐standing controversy about sustained NZG , specifically whether there is a minimum growth rate below which cells die or whether cells enter a non‐growing maintenance state. Using chemostat with cell retention ( CCR ) of P seudomonas putida , we resolve this controversy and show that under NZG conditions, bacteria differentiate into growing and VBNC (viable but not non‐culturable) forms, the latter preserving measurable catabolic activity. The proliferating cells attained a steady state, their slow growth balanced by VBNC production. Proteomic analysis revealed upregulated (transporters, stress response, self‐degrading enzymes and extracellular polymers) and downregulated (ribosomal, chemotactic and primary biosynthetic enzymes) proteins in the CCR versus batch culture. Based on these profiles, we identified intracellular processes associated with NZG and generated a mathematical model that simulated the observations. We conclude that NZG requires controlled partial self‐digestion and deep reconfiguration of the metabolic machinery that results in the biosynthesis of new products and development of broad stress resistance. CCR allows efficient on‐line control of NZG including VBNC production. A well‐nuanced understanding of NZG is important to understand microbial processes in situ and for optimal design of environmental technologies.

Systemic oxygenation weakens the hypoxia and hypoxia inducible factor 1α-dependent and extracellular adenosine-mediated tumor protection - Stephen M. Hatfield; Jorgen Kjaergaard; Dmitriy Lukashev; Bryan Belikoff; Taylor H. Schreiber; Shalini Sethumadhavan; Robert Abbott; Phaethon Philbrook; Molly Thayer; Dai Shujia; Scott Rodig; Jeffrey L. Kutok; et al. (Journal of Molecular Medicine, 2014)